Prevention of cardiovascular events in patients with stable coronary artery disease: myocardial revascularization or pharmacological treatment? - I. S. Yavelov (Кардиоваскулярная терапия и профилактика, 2021)
This review describes the results of randomized, controlled clinical trials comparing the outcomes of stable coronary artery disease after myocardial revascularization and non-invasive treatment, including the recently published results of the International Study of Comparative Health Effectiveness with Medical and Invasive Approaches (ISCHEMIA). New potentials for improving the prognosis in stable coronary artery disease with the help of drug treatment are characterized, the role of which has not yet been evaluated in studies comparing the effectiveness of invasive and conservative approaches to the management of such patients.